Factor Structure and Measurement Invariance of the Brief Symptom Inventory-18 Among Chinese Adults - Geng, Yangwen; Ni, Xiaoli; Wang, Yuping; Fan, Jinming; Qian, Yuyan; Li, Xiaoran (Frontiers in Psychology, 2022)
This study aimed to investigate the factor structure and measurement invariance of the Brief Symptom Inventory-18 (BSI-18) among Chinese adults. A sample of 1839 adults from four cities in Shaanxi province was chosen to finish BSI-18 and background information. The best-fitting factor structure model of BSI-18 was verified by confirmatory factor analyses, and multigroup confirmatory factor analyses were performed to test the measurement invariance. The results indicated that the three-factor bi-factor model fitted the current data best (χ2=468.861, df=117, CFI=0.939, TLI=0.920, RMSEA=0.040, BIC=47044.977). The configural, metric, scalar and strict invariance models all got acceptable model fit indexes across genders, and the configural, metric, scalar invariance models with different living areas and educational levels were all accepted. Overall, the three-factor bi-factor model of BSI-18 fits the Chinese adults well. BSI-18 will be a prospective tool for effectively measuring the mental health among Chinese adults.